The impact of hallux valgus on function and quality of life in females. Issue 4 (June 2022) - Lewis, T.L.; Ray, R.; Gordon, D.J.
Abstract: Background: The effect of hallux valgus (HV) on health-related quality of life (HRQOL) and the relationship between radiographic severity of deformity and patient reported outcome measures (PROMs) is poorly understood. The aim of this study was to compare the HRQOL of female patients with HV to the UK population. The secondary aim was to assess the correlation between PROMs, including HRQOL, with radiographic severity of deformity. Methods: Weight bearing radiographic data (hallux valgus (HVA) angle; intermetatarsal (IM) angle) were measured in consecutive female patients presenting with HV. Each patient prospectively completed the Euroqol EQ-5D-5L questionnaire (EQ-5D), Visual Analogue Scale for Pain (VAS-Pain) and Manchester Oxford Foot Questionnaire (MOXFQ). Data were stratified into age ranges and compared with an EQ-5D United Kingdom general population reference dataset. Pearson R correlation values were calculated for the PROMs and radiographic deformity. Results: Between July 2015 and March 2020, 425 consecutive female patients presented with HV for consideration for surgery. EQ-5D-5L data were prospectively collected for 396 of these patients (93.2%). Females less than 65 years with HV had a statistically significantly worse quality of life compared with females of the same age group in the general population. Above the age of 65, there was no statistically significant difference in EQ-5D-5L Index score between the two groups. Younger females reported higher VAS-Pain scores compared to older patients with 91% of patients reporting some degree of pain symptoms. There was a moderate correlation with MOXFQ Index score and EQ-5D-5L Index (R = −0.51, p < 0.001) and VAS-Pain scores (R = 0.54, p < 0.001). There was no correlation between radiographic HV deformity and HRQOL measures or MOXFQ scores although it was noted that there was a trend of increasing HVA/IMA with age. Conclusion: Female patients presenting with HV deformity have a significantly reduced quality of life compared with the UK general population. The radiographic severity of deformity did not correlate with HRQOL measures or foot and ankle specific PROMs. Foot and ankle specific clinical PROMsmoderately correlate with HRQOL and may be a better marker of the negative effect of symptomatic hallux valgus deformity on quality of life. Level of evidence: III